Agroforestry as nexus of sustainable development goals - Noordwijk, M. van (IOP Publishing, 2020)
Agroforestry, as platform for harmonizing agriculture and forestry in their interactions with landscapes and rural and peri(urban) livelihoods, offers opportunities to benefit from synergies across sustainable development goals (SDGs), and deal with the unavoidable tradeoffs. Such synergy, however, may only emerge if site-specific analysis of the multiple functions of landscapes leads to a shared understanding among stakeholders, clear commitment to common goals, effective means of implementation and a system that remains open to innovation by monitoring functions rather than form, and regularly re-evaluates effectiveness of policy instruments.